Perencanaan Aplikasi Desa Menggunakan Framework Enterprise Architecture Planning (EAP) Pada Kantor Desa Cileungsir - Shofy Nur Khairani, Nabila; Sidiq, Maulana; Mulyana, Dadan (Jurnal Mahasiswa Sistem Informasi Galuh, 2024)
The problem found in the information system at the Cileungsir Village Office, especially the Village BLT, does not yet have an application which can cause it to take a long time and data inaccuracies. By using the Enterprise Architecture Planning (EAP) Framework at the Cileungsir Village Office, this research aims to design a Village Direct Cash Assistance (BLT) application that uses EAP methods. The research methodology used included interviews, observation, and literature study to collect data about the needs and management process of Village BLT at the Cileungsir Village Office. The aim of this application is to integrate the existing information system at the Cileungsir Village Office and make it easier for residents to apply for and manage BLT. In addition, this research shows that information system integration can reduce data duplication and increase data security. Therefore, this research can be a basis for building a more efficient and effective information system to support existing service activities and processes at the Cileungsir Village Office.